Birthplace Diversity and Productivity Spill-Overs in Firms - René Böheim; Thomas Horvath; Karin Mayr (Center for Economic Studies and ifo Institute (CESifo), 2014)
We determine workforce composition and wages in firms in the presence of productivity spill-overs between co-workers. In equilibrium, workers' wages depend on the production structure of firms, own group size, and aggregate workforce composition in the firm. We estimate the wage effects of workforce diversity and own group size by birthplace and the implied production structure in Austrian firms using a comprehensive matched employer-employee data set. In our data, we identify a positive effect of workforce diversity and a negative effect of own group size on wages, which suggest that workers of different birthplaces are complements in production on average.
Keywords: D21; D22; F22; J31; 330; workforce composition; productivity spill-overs; worker group size